Pengaruh Laboratorium Busana Terhadap Keberhasilan Mata Pelajaran Teknologi Menjahit Di SMK Negeri 1 Airmadidi - Missle Jolanda Tumundo; Henny N. Tambingon; Steven Rogahang (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to determine the influence of the fashion laboratory on students’ learning achievement in the Sewing Technology subject at SMK Negeri 1 Airmadidi. The research is grounded in the importance of practical facilities in vocational education, particularly in supporting students’ sewing skills. Although the school provides a fashion laboratory, students’ learning outcomes remain low, with 57.5% failing to meet the Minimum Mastery Criteria (KKM). This research employs a quantitative approach using simple linear regression analysis. The sample consisted of 40 eleventh-grade students majoring in Fashion Design, selected through total sampling. Data were collected through questionnaires measuring students’ perceptions of the fashion laboratory and documentation of semester exam scores as an indicator of learning achievement. The results indicate that the fashion laboratory has a significant influence on students’ academic success. The calculated t-value was 2.544, greater than the critical t-value of 1.686, confirming the acceptance of the alternative hypothesis. The coefficient of determination (R²) was 0.546, meaning that the fashion laboratory contributes 54.6% to learning outcomes, while the remaining 45.4% is influenced by other factors. These findings highlight the critical role of adequate and well-utilized laboratory facilities in supporting effective teaching and learning processes in vocational schools.